Steroids in the gym: the law, strong bodies and masculinity in South Africa - Mashasha, Tamsanqa Munyaradzi (Department of Public Law, 2022)
We know little about the use of steroids in the fitness industry in South Africa although the media frequently features stories about sportsmen who are charged with illegally taking steroids and subsequently issued with bans against continuing to participate in competitive, professional sport. In this study I examine the status of steroids in terms of pharmacology and the law. Steroids is a shorthand for Anabolic-Androgenic Steroids (hereafter AAS). As I show, these substances are evolving compounds with important medical utility but also with the capacity to rapidly build muscle and strength. It is for this reason that they are used in competitive sport but also in the fitness industry where strength and bodily appearance tempt people, mostly men, to take AAS. AAS are defined as a drug and thus cannot legally be bought without a prescription or overthe-counter. But for a number of reasons the control of AAS by regulatory authorities is weak. There are many laws that refer to AAS but these laws overlap and produce inefficiency and consumer confusion. In this grey area, AAS operate as an element of the country's gym culture. The gym as a space for fitness activities has become exceptionally popular in the last few decades. Gyms are primarily a middle class institution, attracting men and women of all races. The desire to get fit and strong and look good is strongly supported by media campaigns. For many men, particularly those that attended sports-focused, single-sex schools, the connection between a fit, strong and good-looking body is an extension of sports participation. For some young men, the habit of taking supplements as part of a fitness regime starts during the school-going years. The line between supplements and AAS is not always clear. This study included a survey of male gym-goers in East London and Cape Town. The survey asked questions about a knowledge and use of AAS and linked these questions to issues of masculinity. The survey was augmented with one-on-one interviews with gym-goers. This primary research is used in a chapter to investigate AAS use amongst gym goers. This thesis compiles and analyses pharmacological and legal material that defines and regulates AAS. To our knowledge this is the first academic work to attempt to understand AAS, their regulation and therefore their accessibility to the public. It shows that because the development of AAS is ongoing in the drug industry, definition is not easy and this, together with the absence of a coordinated set of laws which bear on the production, sale and use of AAS, results in grey areas of uncertainty. The final part of the study is based on a survey of 150 gym users and interviews with a select group of gym users known to the author. Using insider knowledge (the author is himself a gym-user) 30 interviews were conducted. The interviews explore the path along which young men travel as they develop their bodies. This path involves ideas of fitness and strength and these are bound up with the construction of masculine identity. The interviews help to explain why young men seek strong bodies and fitness and why some of these men take or have taken AAS. The thesis argues that the allure of AAS is that it allows young men quickly to build muscle and strength and thus to realize bodily aspirations that are built by the popular media and supported by peer groups. Sport participation is often, but not always, a feature of the bodyfocussed approach to performing a masculine identity. The lack of clarity regarding AAS is a contributing factor to gym-goers using steroids. Steroids can easily be purchased, are widely used and prosecutions for leisure use are unheard of giving the impression that they are not illegal.